Phosphatidylcholine covalently linked to a methacrylate-based monolith as a biomimetic stationary phase for capillary liquid chromatography - Moravcová, Dana; Carrasco-Correa, Enrique Javier; Planeta, Josef; Lämmerhofer, Michael; Wiedmer, Susanne K (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
In this study a strategy to immobilize phospholipids onto a polymer-based stationary phase is described. Methacrylate-based monoliths in capillary format (150×0.1mm) were modified by soybean phosphatidylcholine through 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide coupling to obtain stationary phases suitable to mimic cell surface membranes. The covalent coupling reaction involves the phosphate group in phospholipids; therefore, the described methodology is suitable for all types of phospholipids. Immobilization of soy bean phosphatidylcholine on the monolith was confirmed by attenuated total reflectance Fourier transform infrared spectroscopy and gas chromatography-mass spectrometry of the fatty alcohol profile, generated upon reductive cleavage of the fatty acyl side chains of the phospholipid on the monolith surface with lithium aluminium hydride. The prepared stationary phases were evaluated through studies on the retention of low-molar mass model analytes including neutral, acidic, and basic compounds. Liquid chromatographic studies confirmed predominant hydrophobic interactions between the analytes and the synthesized stationary phase; however, electrostatic interactions contributed to the retention as well. The synthesized columns showed high stability even with fully aqueous mobile phases such as Dulbecco's phosphate-buffered saline solution.
Keywords: Methacrylates; ethyldimethylaminopropylkarbodiimid; methakryláty; Polymers; fosfolipidy; chemické techniky analytické; fosfatidylcholiny; Chromatography, Liquid; Ethyldimethylaminopropyl Carbodiimide; voda; Phosphatidylcholines; Water; biomimetika; Phospholipids; polymery; Biomimetics; chromatografie kapalinová; hydrofobní a hydrofilní interakce; Chemistry Techniques, Analytical; Hydrophobic and Hydrophilic Interactions